UNIQUE ALGORITHM FOR SOLVING OPTIMAL REACTIVE POWER DISPATCH PROBLEM - Dr.K.Lenin (Zenodo, 2017)
In this paper, a new algorithm based on krill herd actions, named as Antarctic krill Herd Algorithm (AKHA) is proposed for solving optimal reactive power dispatch problem. The AKHA algorithm is based on behavior of krill individuals. The minimum distance of each individual krill from food and from uppermost density of the herd are deliberated as the foremost mission for the krill movement. Projected AKHA algorithm has been tested in standard IEEE 30 bus test system and simulation results shows clearly about the good performance of the proposed algorithm in reducing the real power loss and voltage stability also improved.